2022
DOI: 10.1039/d1mh01810h
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic carbon nanotube liquid crystalline elastomer photoactuators for high-definition biomechanics

Abstract: A facile strategy was proposed to prepare intrinsically-photoresponsive elastomer that simultaneously exhibited excellent mechanical toughness, stability and photoresponse. Some high-definition biomechanical applications were successfully demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 82 publications
1
39
0
Order By: Relevance
“…These parameters are of vital importance in biomedical research, disease diagnosis, and timely treatment. Interest in integrated networks of sensors has been motivated by promising applications in intelligent robotics [ 40 42 ], human–machine interactions (HMI) [ 34 , 35 , 43 , 44 ], biomimetic prostheses [ 4 , 45 47 ], smart homes [ 48 50 ], digitizing sports [ 20 , 21 , 51 , 52 ], wireless monitoring in security [ 17 , 23 , 44 , 53 ], and machine learning (ML)-enabled computational sensing platforms [ 54 60 ], promoting the advancement of AI systems. Substantial achievements have been made for pressure sensors, including but not limited to piezoresistive [ 37 , 61 63 ], piezocapacitive [ 64 66 ], transistor [ 48 , 67 , 68 ], piezoelectric [ 25 , 49 , 69 ], and triboelectric sensors [ 31 , 70 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are of vital importance in biomedical research, disease diagnosis, and timely treatment. Interest in integrated networks of sensors has been motivated by promising applications in intelligent robotics [ 40 42 ], human–machine interactions (HMI) [ 34 , 35 , 43 , 44 ], biomimetic prostheses [ 4 , 45 47 ], smart homes [ 48 50 ], digitizing sports [ 20 , 21 , 51 , 52 ], wireless monitoring in security [ 17 , 23 , 44 , 53 ], and machine learning (ML)-enabled computational sensing platforms [ 54 60 ], promoting the advancement of AI systems. Substantial achievements have been made for pressure sensors, including but not limited to piezoresistive [ 37 , 61 63 ], piezocapacitive [ 64 66 ], transistor [ 48 , 67 , 68 ], piezoelectric [ 25 , 49 , 69 ], and triboelectric sensors [ 31 , 70 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1975, Pierre-Gilles de Gennes proposed that LCE, a material capable of producing large stresses and strains under a variety of external stimuli, as one of the most suitable candidates for the manufacture of artificial muscles [ 102 ]. At present, many actuation modes have been constructed to actuate LCE artificial muscles, such as direct-heated [ 103 , 104 , 105 ], electrothermal [ 106 , 107 ] and photothermal [ 108 , 109 , 110 ].…”
Section: Applicationmentioning
confidence: 99%
“…In addition, by mounting LCE strips in parallel with a mouse cardiac trabecula, they showed that it was effective in helping the heart contract, developing a contractile force three times higher than that of human myocardium. Zhang et al [ 109 ] synthesized a photothermal-driven CNT/LCE elastomer. This material can be driven by light in the 200–1200 nm region, and has satisfactory mechanical toughness, drive performance, deformation amplitude, and stability.…”
Section: Applicationmentioning
confidence: 99%
“…, heat or light), 24–40 which are promising for a wide range of applications including artificial muscles, 41–43 soft robotics, 44–47 micromachines 48–50 and biomimetic devices. 51–54 For example, Cai et al 26 reported an LCE-based soft wireless tubular actuator that can achieve multidirectional bending and homogenous contraction. In addition, a remotely controlled bioinspired underwater robot reported by Shahsavan H. et al 55 demonstrates the potential application of LCEs in biomimetic robotics.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling between the alignment of LC molecules and the macroscopic deformation of polymer networks gives rise to unique properties including soft elasticity and large reversible shape changes in response to a stimulus (e.g., heat or light), [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] which are promising for a wide range of applications including artificial muscles, [41][42][43] soft robotics, [44][45][46][47] micromachines [48][49][50] and biomimetic devices. [51][52][53][54] For example, Cai et al 26 reported an LCE-based soft wireless tubular actuator that can achieve multidirectional bending and homogenous contraction. In addition, a remotely controlled bioinspired underwater robot reported by Shahsavan H. et al 55 demonstrates the potential application of LCEs in biomimetic robotics.…”
Section: Introductionmentioning
confidence: 99%